Local Government and Citizen Engagement in Environmental Activism in Spanish and English Cities - Ruiz-Mora, Isabel María; Castillo-Esparcia, Antonio; Barroso, María-Belén (My University, 2016)
Environmental issues have played a part in citizens’ concerns and protests and these issues have played a greater role in political agendas (Levy and Zint, 2013; Dalton, Recchia and Rohrschneider, 2003). As result, grassroots community resistance emerged in response to practices, policies, and conditions that residents have judged to be unfair or illegal (Bullard and Johnson, 2000, p.557). Following the approach of issues management and environmental activism, and considering public relations as a social activity (Ihlen, Fredriksson & van Ruler, 2009), we will investigate if local governments are using issues management “to reduce friction and increase harmony between organisations and their publics” (Heath, 2005, p.460) and how public relations are empowering and engaging citizens to play an active role in their cities' destiny.
Conference poster
Keywords: Medio ambiente - Protección; Administración local; Local government; Environmental activism; Spain; England; Citizen engagement